Relation between physical activity, COVID-19 and immunity: A literature review (Research, Society and Development, 2021)
The aim of this study is based on demonstrating the beneficial effects of regular physical exercise in the face of the COVID-19 pandemic. The article adopted the literature review model, using the PUBMED and GOOGLE SCHOLAR databases, using the Keywords “Coronavirus infections”; “Exercise” and “Physical Condition”. Twenty full articles were selected, in english and portuguese, published from 2019 to the present moment. It was noticed that, with social isolation, the population became more sedentary and adopted less healthy lifestyle habits, however, it was noticed that innate and adaptive immunities are positively affected by physical exercise, providing greater protection against infections, including viroses, such as the Coronavirus. Stimulating the function of imune cells – caused by the practice of the regular physical exercises – neutralizes anxiety and depression, increases lung elasticity and strength, and also minimizes risk factors against contamination by SARS-CoV-2, as well as it can prevent the progression of the disease to severe forms of involvement.